1981
DOI: 10.2135/cropsci1981.0011183x002100050019x
|View full text |Cite
|
Sign up to set email alerts
|

Brown Midrib Mutants in Sudangrass and Grain Sorghum1

Abstract: Three low lignin, brown midrib (bmr) sorghum (Sorghum bicolor L. Moench) mutants, designated bmr‐6, bmr‐12, and bmr‐18, were each backcrossed to normal grain‐ and grassy‐type sorghums. The objective was to determine if the effect of the brown midrib mutants on fiber composition would be expressed equally in both grain‐ and grassy‐type genetic backgrounds.Analysis for fiber composition and in vitro dry matter disappearance (IVDMD) was conducted on mature stem tissue of mutant and normal plants from the F2 gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0
4

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 0 publications
4
16
0
4
Order By: Relevance
“…However, ADF was similar for both types of forage millet. Our results are consistent with other studies that showed lower NDF and ADL for bmr millet, sorghum and corn compared with their normal counterparts (Fritz et al 1981;Cherney et al 1988;Cherney et al 1990). Harvest had no effect on NDF, ADF, and ADL.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…However, ADF was similar for both types of forage millet. Our results are consistent with other studies that showed lower NDF and ADL for bmr millet, sorghum and corn compared with their normal counterparts (Fritz et al 1981;Cherney et al 1988;Cherney et al 1990). Harvest had no effect on NDF, ADF, and ADL.…”
supporting
confidence: 93%
“…Cherney et al (1988) reported 10% higher in vitro DM digestibility for bmr than normal genotype pear millet. Similar improvement in in vitro DM digestibility was reported for bmr sorghum and sudangrass (Fritz et al 1981;Akin et al 1986;Cherney et al 1986). …”
supporting
confidence: 73%
“…Since the brown midrib trait is inherited as a simple recessive trait and is closely associated with improved forage digestibility (Barrière & Argillier 1993, Bittinger et al 1981), forage quality can be improved by fixing bmr alleles. Fritz et al (1981) reported that both grain sorghum and sudangrass (Sorghum sudanense (Piper) Staft), each of which backcrossed with bmr-6, bmr-12 and bmr-18, expressed brown midrib traits and had less lignin content and more digestibility than normal genotypes. Recently, several cultivars bred to contain brown midrib traits have been released (Table 4).…”
Section: Sorghummentioning
confidence: 99%
“…Results were doubtless similar for lignin content. Using three chemically induced mutants, selected by Porter et al [151] for the further experiments, Fritz et al [99] showed an improvement in stem IVDMD ranging between 8 and 12% in brown midrib sorghum, compared to normal sorghum. From their results, the ADL/NDF was reduced by 1.3, 2.2 and 2.5 percent point in bmr6 (BC2), bmr12 and bmr18 (BC1) sorghum, compared to normal, respectively.…”
Section: Genetic Improvement Of Cell Wall Digestibility and Ingestibimentioning
confidence: 99%